2008
DOI: 10.1371/journal.pone.0002827
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resting-State Functional Connectivity in Obese Adolescents; A Magnetoencephalographic Pilot Study

Abstract: BackgroundObesity is not only associated with metabolic abnormalities, but also with cognitive dysfunction and changes in the central nervous system. The present pilot study was carried out to investigate functional connectivity in obese and non-obese adolescents using magnetoencephalography (MEG).Methodology/Principal FindingsMagnetoencephalographic recordings were performed in 11 obese (mean BMI 38.8±4.6 kg/m2) and 8 lean (mean BMI 21.0±1.5 kg/m2) female adolescents (age 12–19 years) during an eyes-closed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Magnetic source imaging suggested a link between increased body weight and pathological alteration in cortical communication processes in the central nervous system among adolescents. 19 White matter lesions in the brain of children younger than 10 years with early onset obesity but not sibling controls was also demonstrated. 20 It is postulated that early exposure to pathological changes in the brain, including alterations in levels of adipokines, hormones or neurotransmitters, may have detrimental effects on the rapid growth of the central nervous system during childhood when the brain is known to be more susceptible to adverse factors.…”
Section: Discussionmentioning
confidence: 93%
“…Magnetic source imaging suggested a link between increased body weight and pathological alteration in cortical communication processes in the central nervous system among adolescents. 19 White matter lesions in the brain of children younger than 10 years with early onset obesity but not sibling controls was also demonstrated. 20 It is postulated that early exposure to pathological changes in the brain, including alterations in levels of adipokines, hormones or neurotransmitters, may have detrimental effects on the rapid growth of the central nervous system during childhood when the brain is known to be more susceptible to adverse factors.…”
Section: Discussionmentioning
confidence: 93%
“…The relationships between OSA and neurocognitive functioning in the obese adolescent population are relatively unexplored. Decreased cognitive functioning among a large sample of obese children has been shown and functional changes have been demonstrated in the brains of obese adolescents compared with lean adolescents (14). However, information is lacking on the additional burden of OSA and whether OSA was a contributing factor to these observations.…”
Section: Discussionmentioning
confidence: 99%
“…A potential interpretation is that the control group increased synchrony over time within specific brain regions as they developed a pattern of excessive synchrony associated with obesity. Cross-sectional studies in both adolescents and adults have indicated that obese participants show greater synchrony between various brain regions compared to their healthier peers (Nummenmaa et al, 2012; Olde Dubbelink et al, 2008). Future studies should compare the longitudinal development of brain function in obese and healthy weight children to investigate these possible differences in developmental trajectories.…”
Section: 1 Conclusionmentioning
confidence: 99%